Pelaksanaan Fungsi Pengawasan Dprd Terhadap Peraturan Daerah Di Provinsi Sulawesi Tengah - Danduru Salurante , Belona; Rustam , Rustam; Naharuddin, Naharuddin; Dewi Primayanti, Andi (Fakultas Hukum Universitas Muhammadiyah Palu, 2025)
Article 18 paragraph (3) of the 1945 Constitution of the Republic of Indonesia stipulates that provincial, regency, and municipal governments each have a Regional People’s Representative Council (DPRD) whose members are elected through general elections. The DPRD works with the regional executive—namely, the regional head—within a system of checks and balances. One manifestation of this system is the DPRD’s supervisory function, including oversight of the implementation of regional regulations. This study employs normative legal research, a documentary approach that analyses legal sources such as statutes, court decisions, legal doctrines, and legal principles. The DPRD of Central Sulawesi Province exercises its supervisory function over regional regulations through two mechanisms: preventive supervision and repressive supervision. These oversight activities aim to ensure that regional regulations are implemented in conformity with applicable laws and the principles of good governance.